Microstrip antenna theory and design - James, James R.; Hall, P. S. (Peter S.); Wood, C. (Colin) (P. Peregrinus on behalf of the Institution of Electrical Engineers, 1981)
The book reviews developments in the following fields: microstrip antenna; flat-plate antenna; microstrip design equations; open circuit microstrip termination; patch antenna; linear array techniques; two-dimensional arrays; and circular polarisation.